Tillichs Method of Correlation: Wessel Stoker in discussion with Dirk-Martin Grube - Stoker, Wessel (NTT, 2020)
The first round of the discussion is on Paul Tillichs famous method of correlation. This method implies that the theological answers are connected with the philosophically-existentialist questions humans ask (rather than being unconnected as in Barthianism). Wessel Stoker worries that this method may privilege Christianity and a particular concept of God over other (quasi-)religions and other concepts in unwarranted ways. Dirk-Martin Grube considers those worries unfounded, given the function Tillich ascribes to this method. In the second round, Stoker insists that the method of correlation is ontologically more heavily loaded than Grube suggests and connects this method with the (religious) a priori. In his response, Grube suggests that Tillichs a priori has different functions than Stoker assumes.